Turn enemies into allies : the art of peace in the workplace : conflict resolution for leaders, managers, and anyone stuck in the middle - Ringer, Judy, 1949- (Career Press, 2019)
In today's workplace, managers, leaders, and HR professionals often believe they don't have the time to help employees navigate conflict. But before you can successfully guide others in managing disagreements, you must be able to manage yourself-- your mindset, presence, and behaviors.Ringer draws on her expertise in conflict and communication skill-building to help readers acquire the skill and confidence to coach conflicting employees back to a professional, effective working relationship, while simultaneously changing their lives for the better. -- adapted from back cover.